The application of reading strategy instruction and its effects on the pre-professional training of the students of medical sciences at the University of Guayaquil. - Mera Velásquez, Francisco David (2018)
The purpose of this research was to establish the students’ use of Reading Strategies at the School of Medical Sciences to acquire competence in medical English. This work used Oxford’s (2011) taxonomy as the foundation for its theoretical frame. This field research was done by means of the Survey of Reading Strategies, an English Reading Motivation Questionnaire, as well as the Background information Questionnaire to collect the students’ information. The research focused on these aspects: a) The use of Metacognitive Strategies, b) the use of Cognitive Strategies, c) The regulation of the affective dimension d) the use of Socio-intercultural strategies. The interpretation of the data revealed that the students did not use enough Metacognitive and Cognitive Reading Strategies, such as analyzing and evaluating the information presented in texts, underlining, highlighting, paraphrasing, and inferring. The students did not regulate their negative affective states, such as anxiety or wrong beliefs, and lacked intrinsic motivation. According to the Social Cognitive Theory (Bandura, 1989), if learning strategies are not practiced often enough, they cannot be retained. Following the application of Reading Strategies, the 25 students from the Experimental Group turned into active readers. Such change was measured quantitatively and qualitatively. The positive findings on reading comprehension improvement, strongly suggest that Reading Strategy Instruction should be included in EFL English lessons to help the learners become independent readers.